KNOWLEDGE OF MODIFIABLE RISK FACTORS OF HEART DISEASE AMONG PATIENTS WITH CARDIOVASCULAR RISK - G, Andhuvan; P, Ayyappan; C, Sahana; S, Poovizhi; K, Sivasakthi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Cardiovascular disease (CVD) is one of the leading killer diseases of people around the world. The purpose of this study was to examine the CVD risk factor and perception among individuals with high CVD risk. Methods: An observational study was conducted for 6 months in the Department of General Medicine of a Multi-Specialty Hospital. Patients who were hypertensive, diabetic, and dyslipidemia with/without comorbid disease were included. Patients who are seriously ill, mentally retarded, physical disabilities, history of CVD, etc., were excluded. CVD risk assessment was done using Framingham risk score, and knowledge assessment was done using knowledge questionnaire on CVD risk. Patient counseling was given to the patients based on their risk and knowledge level and also to improve knowledge about CVD risk and therapeutic goals for the control of blood pressure, blood glucose, lipid profile, and smoking cessation. Results: A total of 100 patients were included in this study comprising 46 males and 54 female. Male has more risk than female. The factors, viz., age, smoking habits, high cholesterol, and diabetes mellitus showed a greater risk in CVD. Knowledge levels assessed in those patients are 28% patients having poor knowledge, 30% patients having fair knowledge, and 42% patients having good knowledge. Conclusion: The study concluded that the participants showed poor knowledge in CVD, which could turn into insufficient preventative behaviors and suboptimal patient outcomes. Pharmacist implementation is needed to assess CVD risk and to improve the health-related quality of life. Keywords: Cardiovascular disease risk, Framingham risk score, Knowledge questionnaire.